Epigenome-Wide Association Study of Soluble Tumor Necrosis Factor Receptor 2 Levels in the Framingham Heart Study - Mendelson, Michael M.; Johannes, Roby; Liu, Chunyu; Huan, Tianxiao; Yao, Chen; Miao, Xiao; Murabito, Joanne M.; Dupuis, Josée; Levy, Daniel; Benjamin, Emelia J.; Lin, Honghuang (Frontiers in Pharmacology, 2018)
Background – Transmembrane tumor necrosis factor (TNF) receptors are involved in inflammatory, apoptotic, and proliferative processes. In the bloodstream, soluble TNF receptor II (sTNFR2) can modify the inflammatory response of immune cells and is predictive of cardiovascular disease risk. We hypothesize that sTNFR2 is associated with epigenetic modifications of circulating leukocytes, which may relate to the pathophysiology underlying atherogenic risk. Methods – We conducted an epigenome-wide association study of sTNFR2 levels in the Framingham Heart Study Offspring cohort (examination 8; 2005-2008). sTNFR2 was quantitated by enzyme immunoassay and DNA methylation by microarray. The concentration of sTNFR2 was loge-transformed and outliers were excluded. We conducted linear mixed effects models to test the association between sTNFR2 level and methylation at over 400,000 CpGs, adjusting for age, sex, BMI, smoking, imputed cell count, technical covariates, and accounting for familial relatedness. Results – The study sample included 2468 participants (mean age: 67±9 years, 52% women, mean sTNFR2 level 2661±1078 pg/ml). After accounting for multiple testing, we identified 168 CpGs (P<1.2x10-7) that were differentially methylated in relation to sTNFR2. A substantial proportion (27 CpGs; 16%) are in the major histocompatibility complex region and in loci overrepresented for antigen binding molecular functions (P=1.7x10-4) and antigen processing and presentation biological processes (P=1.3x10-8). Identified CpGs are enriched in active regulatory regions and associated with expression of 48 cis-genes (±500kb) in whole blood (P<1.1x10-5) that coincide with genes identified in GWAS of diseases of immune dysregulation (inflammatory bowel disease, type 1 diabetes, IgA nephropathy). Conclusions –Differentially methylated loci in leukocytes associated with sTNF2 levels reside in active regulatory regions, are overrepresented in antigen processes, and are linked to inflammatory diseases.